Evaluation of liquid and powdered forms of polyclonal antibody preparation against Streptococcus bovis and Fusobacterium necrophorum in cattle adapted or not adapted to highly fermentable carbohydrate diets - Cassiano, Eduardo Cuellar Orlandi; Junior, Flavio Perna; Barros, Tarley Araújo; Marino, Carolina Tobias; Pacheco, Rodrigo Dias Lauritano; Ferreira, Fernanda Altieri; Millen, Danilo Domingues [UNESP]; Martins, Mauricio Furlan; Pugine, Silvana Marina Piccoli; De Melo, Mariza Pires; Beauchemin, Karen Ann; Meyer, Paula Marques; et al. (Asian Australasian Association of Animal Production Societies, 2021)
Objective: Feed additives that modify rumen fermentation can be used to prevent metabolic disturbances such as acidosis and optimize beef cattle production. The study evaluated the effects of liquid and powdered forms of polyclonal antibody preparation (PAP) against Streptococcus bovis and Fusobacterium necrophorum on rumen fermentation parameters in ruminally cannulated non-lactating dairy cows that were adapted or unadapted to a high concentrate diet. Methods: A double 3×3 Latin square design was used with three PAP treatments (control, powdered, and liquid PAP) and two adaptation protocols (adapted, unadapted; applied to the square). Adapted animals were transitioned for 2 weeks from an all-forage to an 80% concentrate diet, while unadapted animals were switched abruptly. Results: Interactions between sampling time and adaptation were observed; 12 h after feeding, the adapted group had lower ruminal pH and greater total short chain fatty acid concentrations than the unadapted group, while the opposite was observed after 24 h. Acetate:propionate ratio, molar proportion of butyrate and ammonia nitrogen concentration were generally greater in adapted than unadapted cattle up to 36 h after feeding. Adaptation promoted 3.5 times the number of Entodinium protozoa but copy numbers of Streptococcus bovis and Fibrobacter succinogens genes in rumen fluid were not affected. However, neither liquid nor powdered forms of PAP altered rumen acidosis variables in adapted or unadapted animals. Conclusion: Adaptation of cattle to highly fermentable carbohydrate diets promoted a more stable ruminal environment, but PAP was not effective in this study in which no animal experienced acute or sub-acute rumen acidosis.
Keywords: Acute Phase Protein; Feed Additive; Passive Immunization; Real-time Polymerase Chain Reaction; Rumen Fermentation